The Effectiveness of Powtoon Animation Media on Student Learning Outcomes in Human Respiratory System Subject - Firman, Reema Lee; Ningsih, Kurnia; Panjaitan, Ruqiah Ganda Putri (Asian Journal of Science Education, 2023)
Powtoon is an online application that can be used as a learning medium. This study aims to determine the effectiveness of using powtoon animation media on student learning outcomes in the human respiratory system in Eight-grade Junior High School 3 Pontianak. The method used in this research is Quasi Experimental with Pre-test Post-test Control Group Design. The samples used were 2 classes, namely the experimental class with 31 students and the control class with 32 students, which were taken using the intact group technique. The instrument used was a multiple choice test totaling 20 questions. Learning outcome data was analyzed using the independent sample t-test. The average post-test result for the experimental class was 76.56, which was higher than the control class, which was 69.53. The effect size calculation obtained is 0.70 which is included in the medium category and contributes 25.80% in learning, so it can be concluded that powtoon animation media influences student learning outcomes